Halitose: etiologia, diagnóstico e perspectivas - Alves, Tatiana Yshioka [UNESP] (2010)
Halitosis is the unpleasant odor emanating from oral and nasal cavities and it can be classified in physiologic, pseudo-halitosis and pathological. It causes a embarrassing and discomfort situation to the patients. The etiology of halitosis including systemic and oral factors. So, the oral health is showed like a essential factor that promote the health of person, in the biologic, psychological, social and cultural aspects. Among the oral causes of halitosis is found the production of Volatile Sulfur Compounds (VSC) for bacteria, mainly Gram-negative. Tongue coating, with a extensive surface and anatomical variations, accumulate rest of food e microorganisms and periodontal disease result in necrosis of periodontal tissues with intense metabolism of bacteria are causes of halitosis. Systemic disturbs can interview in the oral breath of the patient like reflux and gastro-esophageal disease, metabolic and hormonal alterations (menstrual cycle, diabetes), medication and treatments (imunosupressors drugs, radiotherapy) which causes alterations in the salivary flux and contribute for halitosis as well as style of life (diet, habit, vice) and emotional state (anxiety, stress, depression). The diagnosis is complex and determinant for the treatment. A successful treatment depends of correct diagnosis, considering the oral and systemic etiology, and interaction of a team of multidisciplinary professionals, including dental surgeon, doctors like gastroenteologists, psychiatrists, nutritionists and psychologists